Love in İsmet Özel’s Poetry in the Context of the Ashiq-Mashuq-Raqib - Emrullah Yakut (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
The existential adventure of man, shaped by the driving forces of the nafs [commanding self], reason, and love, has been largely reflected in literary texts, particularly poetry, which are also products of man’s linguistic expression. Although this expression has some superficial differences in different literary traditions, it also has some aspects in common. The love theme in classical poetry between the lover–beloved–rival [ashiq, mashuq, raqib] trio manifests itself in similar forms in İsmet Özel’s poetry. There is a transition in classical poetry between metaphorical and true love that frequently obscures the boundaries and renders the distinctions meaningless. Meanwhile, in Özel’s poetry, love is intertwined with ideological goals and sensual desires, with sharp transitions between them. In classical poetry, love is an important means of human evolution. Similarly, for İsmet Özel, love is an act that leads people to the leap of existence. İsmet Özel’s poetry draws attention with a strong emphasis on “self,” whereas in classical poetry, the lover almost destroys his own self (fenâ) and attains the beloved. However, the clues that allow this self to be understood as a beloved one elevate the issue to a more interesting level within the framework of the lover–beloved unity known in classical poetry and mysticism. This article aims to compare the concept of love and the manifestations of lover, beloved, and rival in classical poetry and İsmet Özel’s poetry, in order to identify and analyze the similarities and differences.